1994
DOI: 10.1128/jvi.68.6.4086-4091.1994
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of virus-like particles containing rubella virus structural proteins

Abstract: Rubella virus (RV) virions contain two envelope glycoproteins (El and E2) and a capsid protein (C). Noninfectious RV-like particles (VLPs) containing three structural proteins were expressed in a BHK cell line (BHK-24S) by using an inducible promoter. These VLPs were found to resemble RV virions in terms of their size, their morphology, and some biological activities. In immunoblotting studies, VLPs were found to bind similarly to native RV virions with 10 of a panel of 12 RV-specific murine monoclonal antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…First, replicons which express only the nonstructural proteins and replicate the replicon RNA (Tzeng et al, 2001) can be used to determined if the nonstructural proteins and the process of RNA replication is sufficient for attracting the RER, mitochondria, and Golgi to the CVs. Second, it has been found that expression of structural proteins results in formation of virus-like particles (VLPs) that are similar in all aspects, including morphology, to virions Qiu et al, 1994). While VLPs do not contain genome RNA, it is not unequivocally clear whether they incorporate cellular RNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…First, replicons which express only the nonstructural proteins and replicate the replicon RNA (Tzeng et al, 2001) can be used to determined if the nonstructural proteins and the process of RNA replication is sufficient for attracting the RER, mitochondria, and Golgi to the CVs. Second, it has been found that expression of structural proteins results in formation of virus-like particles (VLPs) that are similar in all aspects, including morphology, to virions Qiu et al, 1994). While VLPs do not contain genome RNA, it is not unequivocally clear whether they incorporate cellular RNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular significance is the development of cDNA constructs that express RV structural proteins that assemble into rubella virus-like particles (RLP). These RLPs have similar morphology and sites of budding to their wild-type counterpart, and they serve as a convenient tool in dissecting the RV assembly pathway (58,126). For RV, the assembly of structural proteins begins immediately following translation of these proteins.…”
Section: Structural Proteins: Translation Processing and Assemblymentioning
confidence: 99%
“…The role of the capsid protein in RV assembly is less well defined. It has been proposed that maintenance of the E2 signal sequence as part of the capsid protein after cleavage allows the capsid protein to be transported along with the glycoproteins to the Golgi complex (126). Earlier studies postulated that the interaction of the E1 cytoplasmic domain and the RV capsid protein triggered virus budding (58).…”
Section: Structural Proteins: Translation Processing and Assemblymentioning
confidence: 99%
“…These posttranslational events in antigen formation may be particularly important in the synthesis of envelope glycoprotein structures, especially those that are heterodimeric. Production of recombinant DNA-derived viral surface proteins in a viruslike particulate form using eukaryotic cells has been reported for several enveloped viruses (1,4,5,26,27,(31)(32)(33). Since virion maturation may be driven by the ability of the individual envelope proteins to self-assemble, some viral proteins may self-assemble and be released from cells transfected with their genes, greatly facilitating their production and purification.…”
mentioning
confidence: 99%